Interparticle Distance Variation in Semiconductor Nanoplatelet Stacks (Adv. Funct. Mater. 24/2022). (8th June 2022) - Graf, Rebecca T.; Schlosser, Anja; Zámbó, Dániel; Schlenkrich, Jakob; Rusch, Pascal; Chatterjee, Atasi; Pfnür, Herbert; Bigall, Nadja C.
Abstract : Semiconductor Nanoplatelet Stacks In article number 2112621, Nadja C. Bigall and co‐workers demonstrate a route to decrease the inter‐nanoplatelet distance in polymer encapsulated cadmium chalcogenide nanoplatelet stacks. Thus, certain ligand exchanges are applied to minimize the distance by more than half in the case of CdSe nanoplatelets. Furthermore, the influence of the smaller distance on the charge carrier transfer is analysed by photo‐electrochemical measurements.